Expendable dominant as the foundation of formation income of hunting economy - Vinichenko, Ihor; Вініченко, Ігор Іванович; Polehenka, Maryna; Полегенька, Марина Анатоліївна (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
The article examines the costly dominant as the foundation of the formation of the income of hunting farms. The maximum permissible amount of expenditure of funds of hunting farms for the use of agricultural land for the lease of hunting grounds, game breeding and animal protection is presented. It is substantiated that the use of methods of system analysis, namely SVR-analysis and LCC-analysis, allows to combine economic, ecological and social components of expenditure dominants of formation of income of hunting farms and to predict the ratio of income and costs associated with strategic vision of their structure in the context of dynamic influence of ecological and economic factors, which change the level of effective use of the natural landscape of hunting farms and their transformational characteristics. The interdependence of indicators and factors of influence on efficiency of hunting industry is determined. It has been proved that the cost approach allows to accumulate the total amount of resources involved in the economic turnover of hunting farms for updating the bio system of hunting grounds, protecting varieties of game and animals. The costresourcedominant of the formation of the income of hunting farms combines the costs of developing agricultural land for hunting grounds and ensuring the optimal density of wild animals per 1 hectare of forest forest area. The norms of extraction of individual species of hunting animals with their optimal number from the forest area are substantiated. The expenses and income of hunting farms are grouped on average by one forestry region of Ukraine. The share of costs for wildlife protection is determined and the percentage of rent for 1 ha of agricultural land for biomass reproduction and game breeding is ordered. The permissible norms for the use (shooting, trapping) of certain species of hunting animals in the regions of Ukraine have been established. The value resource dominant value in the formation of revenues of hunting farms is determined, which has a direct relationship between raising funds for the use of leased agricultural land plots for hunting grounds and their distribution in the total costs of hunting farms. В статті досліджено витратну домінанту як фундамент формування доходів мисливських господарств. Представлено гранично допустиму величину витрат коштів мисливських господарств для використання земель сільськогосподарського призначення під оренду мисливських угідь, розведення дичини та охорони тварин. Обгрунтовано, що використання методів системного аналізу, а саме СVР-аналізу та LCC-аналізу, дозволяє поєднувати економічні, екологічні та соціальні складові витратної домінанти формування доходів мисливських господарств та прогнозувати співвідношення доходів і витрат, пов'язаних із стратегічним баченням їх структури в контексті динамічного впливу еколого-економічних чинників. Визначено взаємозалежність показників та факторів впливу на ефективність ведення мисливської галузі. Доведено, що витратний підхід дозволяє акумулювати загальну величину залучених ресурсів вгосподарський обіг мисливських господарств для оновлення біосистеми мисливських угідь, охорони різновидів дичини та тварин. Вартісно-ресурсна домінанта формування доходів мисливських господарств поєднує витрати на освоєння земель сільськогосподарського призначення під мисливські угіддя та забезпечення оптимальної щільностідиких тварин на 1 га лісомисливської площі. Обгрунтовано норми вилучення окремих видів мисливських тварин приоптимальній їх чисельності з лісомисливської площі. Згруповано витрати та доходи мисливських господарств в середньому на один лісомисливський регіон України. Визначено частку витрат на охорону диких тварин та впорядковано відсоток орендованої плати за 1 га ділянки земель сільськогосподарського призначення на відтворення біомасита розведення дичини. Встановлено допустимі норми використання (відстрілу, відлову) окремих видів мисливськихтварин в регіонах України. Визначено величину вартісно-ресурсної домінанти у формуванні доходів мисливських господарств, яка має пряму залежність між залученням коштів на використання орендованих земельних ділянок сільськогосподарського призначення під мисливські угідь та їх розподілу в загальних витратах мисливських господарств.
Витратна домінанта як фундамент формування доходів мисливських господарств
Keywords: expenses; витрати; income; доходи; hunting grounds; мисливські угіддя; rent; оренда; agricultural lands; землі сільськогосподарського призначення; wild animals; дикі тварини; biodiversity protection; охорона біорозмаїття